PORTRAIT OF RISK MANAGEMENT AS AN EFFORT TO PREVENT CORPORATE FINANCIAL FRAUD - Faisol, Faisol; Haryansyah, Septian Eko; Islamy, Sulaiha Nor; Zulviar Anas (Jurnal Akuntansi, Keuangan, Perpajakan dan Tata Kelola Perusahaan, 2024)
Risk management is a methodological approach in managing uncertainty related to the threat of organizational loss. If risk management is connected to fraud, it will have a positive impact which can provide prevention of fraud. This research aims to determine the role of risk management as an effort to prevent corporate financial fraud. This research uses a literature review approach by analyzing various journals, previous national and international articles related to the role of risk management in preventing financial fraud. The results of this research show that from various journals, previous research articles that have been analyzed show that the implementation of risk management has a positive impact on companies so that risk management can help in preventing financial fraud. The results of this research can provide more benefits to companies so they can implement risk management to minimize the occurrence of financial fraud.